(untitled) (UNIZIK Journal of Educational Management and Policy, 2024)
This study focused on ascertaining the relationship between financial resource planning and accreditation outcome in tertiary institution in Anambra State, Nigeria. A co-relational research design was adopted. The population of the study stood at 320 respondents which comprised all heads of academic departments in tertiary institutions in Anambra State. A sample size of 135 heads of departments that carried out accreditation in at least one programme in the year 2021, 2022 and 2023 were selected for the study. A structured questionnaire titled Financial Resource Planning Questionnaire (FRPQ), with eleven items was used for data collection. The face validity of the questionnaires was determined by three experts, while the internal consistency of the instrument was determined using Cronbach’s Alpha reliability coefficient, of which 0.89 was obtained. The researcher together with 18 research assistants that lectures in the various institutions administered the instruments directly to the respondents. The data collected were analyzed using Pearson’s Product Moment Correlation Coefficient to answer the research question and multi-nominal logistic regression to test the null hypothesis at 0.05 level of significance. The decision to reject or fail to reject the hypothesis was based on probability value (p-value). Where the p-value was less than the stipulated level of significance (0.05), the null hypothesis was rejected, whereas the null hypothesis was not rejected where the calculated p-value is greater than the stipulated level of significance (0.05). The analysis was done using Statistical Package for Social Science (SPSS) version 21. The findings of the study show that there was low positive relationship between financial resource planning and accreditation outcome in tertiary institutions in Anambra state. It was therefore concluded that there was a significant relationship between financial resource planning and accreditation outcome in tertiary institutions in Anambra state. Among the recommendation is that taxes such as education tax or rate to be imposed on all workers in the government and private sectors and money realized will be used to provide human, technical and material resources that are lacking in tertiary institutions.